Borrelia Isolates in Northern Colorado Identified as Borrelia bissettii - Schneider, Bradley S. (American Society for Microbiology, 2000)
Previous work described Borrelia burgdorferi sensu lato group DN127 as a new genospecies, Borrelia bissettii, and prompted the present study to identify the Borrelia spp. that exist in northern Colorado. To determine the genospecies present, we analyzed two specific intergenic spacer regions located between the 5S and 23S and the 16S and 23S ribosomal genes. Phylogenetic analysis of the derived sequences clearly demonstrated that these isolates, originating from rodents captured in the foothills of northern Colorado, diverged from B. burgdorferi sensu stricto by 5 to 5.5% and were members of the new genospecies B. bissettii.